2011
DOI: 10.1124/jpet.111.185173
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Estrogen Sulfotransferase Expression by Confluence of MCF10A Breast Epithelial Cells: Role of the Aryl Hydrocarbon Receptor

Abstract: Estrogen sulfotransferase (SULT1E1) catalyzes the sulfonation of estrogens, which limits estrogen mitogenicity. We recently reported that SULT1E1 expression is low in preconfluent MCF10A human breast epithelial cells but increases when the cells become confluent. Pulse-chase labeling experiments with 5-bromouridine demonstrated that the confluence-mediated increase in SULT1E1 expression was due to increased mRNA synthesis. Because aryl hydrocarbon receptor (AhR) activation has been shown to suppress SULT1E1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
(49 reference statements)
2
7
0
Order By: Relevance
“…When the breast cells switch to a proliferative state, a lessening of cell-cell contact causes activation of AhR activity and suppression of SULT1E1 expression in tumor as found in our studies (Fig. 3), resulting in increased active estrogen levels in the breast microenvironment [74], interestingly it was found that arsenic-induced AhR activation and -enhanced CYP1A1 expression can be further increased by a pro-oxidant, buthionine-(S,R)sulfoximine, and suppressed by antioxidants, such as N-acetylcysteine and catalase [75] leading to the conclusion that AhR is active under oxidative stress which may suppress SULT1E1 expression.…”
Section: Discussionsupporting
confidence: 65%
“…When the breast cells switch to a proliferative state, a lessening of cell-cell contact causes activation of AhR activity and suppression of SULT1E1 expression in tumor as found in our studies (Fig. 3), resulting in increased active estrogen levels in the breast microenvironment [74], interestingly it was found that arsenic-induced AhR activation and -enhanced CYP1A1 expression can be further increased by a pro-oxidant, buthionine-(S,R)sulfoximine, and suppressed by antioxidants, such as N-acetylcysteine and catalase [75] leading to the conclusion that AhR is active under oxidative stress which may suppress SULT1E1 expression.…”
Section: Discussionsupporting
confidence: 65%
“…Effects of Lipid-and Xenobiotic-Sensing Receptor Activators on SULT Expression in HepaRG Cells. To identify nuclear signaling pathways that regulate SULT expression in the HepaRG model of human liver cell differentiation, cells were treated for 48 hours with activators of the AhR and several lipid-and xenobiotic-sensing nuclear receptors that have been reported to regulate SULT expression in other human cell systems (Song et al, 2001;Fang et al, 2005Fang et al, , 2007Jiang et al, 2005;Fu et al, 2011;Rondini et al, 2014;Barrett et al, 2016;Dubaisi et al, 2016). Both confluent and differentiated HepaRG cells were treated to consider the possibility that cells in the two stages could differ in their responses due to differences in their content of transcriptional machinery.…”
Section: Expression and Regulation Of Sults In Primary Cultures Ofmentioning
confidence: 99%
“…SULT expression is regulated by lipid-and xenobiotic-sensing receptors, including aryl hydrocarbon receptor (AhR), constitutive androstane receptor, pregnane X receptor (PXR), liver X receptor (LXR), farnesoid X receptor (FXR), peroxisome proliferator-activated receptors (PPARs), and vitamin D receptor (VDR) in a species-and tissue-specific manner (Echchgadda et al, 2004a,b;Fang et al, 2005Fang et al, , 2007Jiang et al, 2005;Fu et al, 2011;Kodama et al, 2011;Sueyoshi et al, 2011). Most studies of human SULT regulation have been performed using primary cultures of adult human hepatocytes (Fang et al, 2005(Fang et al, , 2007Uppal et al, 2007), or hepatic or extrahepatic cell lines (Song et al, 2001;Higashi et al, 2004;Jiang et al, 2005;Fu et al, 2011;Rondini et al, 2014;Barrett et al, 2016;Dubaisi et al, 2016), but none have been performed using human fetal hepatocytes or culture models of human liver cell differentiation. Consequently, little is known about the mechanisms that regulate SULT expression during human liver development.…”
Section: Introductionmentioning
confidence: 99%
“…Another group reported expression of SULT 1E1 mRNA alone in MCF-10A cells and observed both epigenetic regulation of SULT 1E1 mRNA and repression in transformed MCF-10A-derived cells (39). There is some evidence to suggest that SULT 1E1 gene transcription is mediated via the aryl hydrocarbon receptor in MCF-10A cells (55). In addition, there may be an association between breast cancer and genetic polymorphisms in human UGT1A1, another key mediator of conjugative metabolism (56).…”
Section: Discussionmentioning
confidence: 99%